The crime prevention effect of CCTV in public places: a propensity score analysis - Piza, Eric L. (Journal of crime and justice, 2018)
This study measures the effect of CCTV in Newark, NJ across three separate crime categories: auto theft, theft from auto, and violent crime. CCTV viewsheds, denoting camera line-of-sight, were units of analysis. Viewsheds for treatment units were created by digitizing live CCTV footage within a geographic information system (GIS). Control viewsheds were created with GIS tools and aerial imagery from Google maps. Treatment cases were matched with control cases via propensity score matching (PSM) to ensure statistical equivalency between groups. Effect was measured via odds ratios and average treatment on the treated statistics. Findings offer modest support for CCTV as a deterrent against auto theft while demonstrating no effect on the other crime types. These results suggest that CCTV appears to be a viable option for jurisdictions wishing to target auto theft. Agencies suffering from other street-level crime problems may not benefit from CCTV and may need to deploy CCTV alongside other evidence-based strategies, rather than as a stand-alone tactic, in order to achieve crime control benefits.